(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
Insurance is a fertile field for acquiescence, and the insured as an acquiescent cannot reject the condition of the contract even if he is aware of it and was aware of the extent of the unfairness to which he is subjected. Acquiescence by its nature means submission and inability to discuss the conditions imposed. Therefore, all the terms of the contract of acquiescence are similar for the acquiescent, as he acquiesces to all the terms of the contract without distinguishing between the conditions of which he is aware and those to which he does not pay attention. Therefore, the attribution of the quality of acquiescence to a contract is very important for the weak party for the purpose of benefiting from protection, which aims to restore the legal and economic balance of the contract, as enshrined by the Algerian Civil Code by granting an authorization to the judge to intervene in the contractual content, in a violation of the contracting principle. Despite the fact that this principle has been proven for many centuries, the provisions of Article 110, 111 and 112 of the Civil Code constituted a turning point which allowed the presence of other parties that could limit the freedom of contractors to set the terms of their contracts. Thus, the judge is an important party which is allowed to intervene to interpret, amend or delete a clause that is considered arbitrary; this is what we will discuss in practice through the insurance contract. Key words- Contract of Acquiescence, Contractual balance, Intervention of the Judge, Insurance Contract